2019
DOI: 10.1021/acs.energyfuels.9b02609
|View full text |Cite
|
Sign up to set email alerts
|

Nanofluid of Petroleum Sulfonate Nanocapsules for Enhanced Oil Recovery in High-Temperature and High-Salinity Reservoirs

Abstract: Petroleum sulfonate (PS) salt surfactants that are insoluble in high-salinity water were encapsulated into 10–60 nm oil swollen micelles dispersed by a cocamidopropyl hydroxysultaine zwitterionic cosurfactant to form a highly stable nanofluid at elevated salinity (∼56 000 mg/L) and temperature (∼100 °C). The resulting “Nano-Surfactant (NS)” fluid enables an economic, efficient, and environmentally friendly enhanced oil recovery (EOR) capable of targeted delivery of PS salt surfactantsone of the most abundant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 29 publications
0
20
0
Order By: Relevance
“…Calcium carbonate (CaCO 3 ) is a widely important mineral that is found extensively in biological and geological systems. The interaction of water, ions, organic molecules, macromolecules, and nanomaterials with calcite surfaces controls a broad range of natural and industrial processes such as ion exchange, contaminant migration, , enhanced oil recovery, biomineralization, and flocculation . Atomic force microscopy (AFM) is a powerful tool to study calcite surface interactions in air and in solution because of its Angstrom-level spatial and pico-Newton force resolutions.…”
Section: Introductionmentioning
confidence: 99%
“…Calcium carbonate (CaCO 3 ) is a widely important mineral that is found extensively in biological and geological systems. The interaction of water, ions, organic molecules, macromolecules, and nanomaterials with calcite surfaces controls a broad range of natural and industrial processes such as ion exchange, contaminant migration, , enhanced oil recovery, biomineralization, and flocculation . Atomic force microscopy (AFM) is a powerful tool to study calcite surface interactions in air and in solution because of its Angstrom-level spatial and pico-Newton force resolutions.…”
Section: Introductionmentioning
confidence: 99%
“…Recent experiments have identified that trace amount of mineral oils may result in better high salinity colloidal stability of the surfactant mixtures . We hypothesize that the inclusion of oils (decane) can form larger oil-swollen micelles with stronger cosurfactant shielding (Figures D,E and B,D) compared to smaller micelles with weaker cosurfactant shielding (Figures B,C and B) for the sulfonates and resulted in more colloidally stable formulations in high salinity.…”
Section: Resultsmentioning
confidence: 81%
“…Phase 2 of the microfluidic experiments was aimed to further evaluate the best-performing formulations from Phase 1 in singlicate: Duomeen TTM, Amphosol LB, and Amphosol CG-50. Petrostep SB was also selected for further evaluation due to its zwitterionic chemical structure with favorable stability and transport properties in high-salinity and high-temperature carbonate reservoirs 48 . In Phase 2 of the experiments, CO 2 foams were evaluated at surfactant concentrations of 0.5, 0.2, 0.1, and 0.05 wt% in Brine 1, at 50%, 70%, and 80% foam qualities.…”
Section: Phase 2: Sensitivity Analysis Of the Foam To Concentration Omentioning
confidence: 99%